Who Follows the Rules During a Crisis?—Personality Traits and Trust as Predictors of Compliance With Containment Recommendations During the COVID-19 Pandemic - Schmeisser, Yvonne; Renström, Emma A.; Bäck, Hanna (Frontiers in Political Science, 2021)
When the COVID-19 pandemic hit in 2020, many governments tried to contain the spread of the virus by legally restricting social life and imposing national lockdowns. The Swedish government did not enforce a national lockdown, but instead appealed to the individual’s self-responsibility to follow specific containment recommendations developed by the Swedish Public Health Agency. Sweden is thus an especially interesting case to study because of the potential influence of psychological and attitudinal individual-level factors that might contribute to compliance with containment recommendations. Drawing on previous literature on how individuals respond during health crises, we define and evaluate a mediation model that considers the role of personality traits and trust authorities to explain compliance. More specifically, we argue that we need to consider the role of trust in authorities to better understand the relationship between personality traits and compliance. In analyses based on a large-scale representative survey (N = 1,034), we find Conscientiousness to be directly linked to compliance, whereas Agreeableness, Neuroticism and Openness were indirectly related to compliance when trust in the Public Health Agency was taken into account.